Islamic Education Teachers’ Adaptation in Digital Learning during the Covid-19 Pandemic - Sarah Aisha; Ahmad Zuhdi Firdaus; Deddy Mulyana (MediaTor (Jurnal Komunikasi), 2022)
The Covid-19 pandemic has disrupted educational communication, as traditional teaching and learning have been replaced by online digital teaching and learning. Thus, teachers must adapt quickly to new technology to meet the lesson objectives and successfully deliver their lessons. This study explores teachers’ adaptation experience throughout the Covid-19 pandemic. Data was gathered in Mutiara Bunda Elementary School, an inclusive private school in Bandung with religious education at its core. In-depth interviews and introspection were conducted with four Islamic education teachers across grades. Thematic analysis was used to analyse the data. The findings revealed that teachers went through five overlapping stages: confusion, trial and error, capacity building, adaptation, and efforts to find new solutions. However, different challenges were faced by each teacher according to the grades they taught. Even though teachers had finally adapted and transformed the teaching and learning experience, traditional face-to-face communication was still preferred by 1st to 3rd-grade teachers to deliver the lessons effectively. Lack of the teachers’ IT skills to deliver the lessons to develop the students’ character, inexperience in online teaching, and the students’ low motivation to learn through the digital platform clearly constitute the main obstacle in this religious, educational process.